Two And Twenty Troubles - Ilyukhin, Victor (USA, 2016)
Two disabled actors (both amputees), intend to restart their career after a long hiatus. Rachel was a promising young actress before surviving a car accident two years ago. Anthony was born with his physical disability and has been taking a break from acting due to a persistent lack of confidence. Both meet each other at the Nicu's Spoon Theater - a company whose mission is to give an opportunity to both disabled and non-disabled actors of various ages, gender, races and cultural backgrounds alike.
Keywords: Documentary films